Performance of mycelium composites of Lentinus crinitus under two compression protocols - César, Enrique; Montoya, Leticia; Bárcenas-Pazos, Guadalupe M.; Ordóñez-Candelaria, Víctor R.; Bandala, Víctor M. (Instituto de Ecología, A.C., 2021)
Considering the current environmental problems that has been generated by the excessive production of synthetic plastics, more sustainable alternatives have been proposed. One of these recently studied materials are the mycelium composites, a product obtained with lignocellulosic particles agglomerated together by the myceliar growth of a filamentous fungus. This novel type of materials could represent an option to replace non-biodegradable materials. In this work, mycelium composites with characteristics comparable to expanded polystyrene (EPS) and potentially suitable for fabrication of insulation panels were developed using a Lentinus crinitus strain previously selected after mycelial phases tests. Mechanical variables in bending, compression strength and stiffness were measured following ASTM D143 standard. Two protocols for composite fabrication were followed using different compression loads. Flexural strength reached 0.48 MPa and compression strength 0.235 MPa. Results obtained were compared with data of balsa wood (Ochroma pyramidale) for the similarity of possible applications, expanded polystyrene as its possible substitute and early published data on mycelium composites. Mechanical performance in flexural and compressive strength of the obtained materials revealed their potential use as biodegradable alternatives to some applications of synthetic plastics as insulation panels and packing materials.